THE SUCCESSFUL MODEL OF DISTANCE LEARNING - D. Branekova (Trakia Journal of Sciences)
The main focus of the article is the presentation of a model of distance learning in the process of its implementation in the conditions of a global pandemic. A study is included related to the readiness of teachers and students to implement distance learning without time for prior preparation. The influence of the model has been studied on the readiness of the students for learning, as well as the student's attitude to distance learning. Recommendations are made for the development and improvement of the model of distance learning as a component of the university educational environment.